2013
DOI: 10.1007/s10877-013-9497-7
|View full text |Cite
|
Sign up to set email alerts
|

A pilot study quantifying the shape of tidal breathing waveforms using centroids in health and COPD

Abstract: During resting tidal breathing the shape of the expiratory airflow waveform differs with age and respiratory disease. While most studies quantifying these changes report time or volume specific metrics, few have concentrated on waveform shape or area parameters. The aim of this study was to derive and compare the centroid co-ordinates (the geometric centre) of inspiratory and expiratory flow-time and flow-volume waveforms collected from participants with or without COPD. The study does not aim to test the diag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
41
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(43 citation statements)
references
References 18 publications
2
41
0
Order By: Relevance
“…The current study also revealed a marked shortening of inspiratory time (ie, median tI) in the COPD cohort, and, as a consequence, ratios derived from this parameter (tI/tE and tI/tTot) were also reduced. A similar shortening of tI and associated ratios was recorded in COPD patients who participated in earlier studies employing PNT or OEP to measure tidal breathing 6,8,10. Also, the median tPTEF SLP /tE was reduced in patients with COPD compared with healthy subjects.…”
Section: Discussionsupporting
confidence: 73%
See 3 more Smart Citations
“…The current study also revealed a marked shortening of inspiratory time (ie, median tI) in the COPD cohort, and, as a consequence, ratios derived from this parameter (tI/tE and tI/tTot) were also reduced. A similar shortening of tI and associated ratios was recorded in COPD patients who participated in earlier studies employing PNT or OEP to measure tidal breathing 6,8,10. Also, the median tPTEF SLP /tE was reduced in patients with COPD compared with healthy subjects.…”
Section: Discussionsupporting
confidence: 73%
“…A number of studies have reported that patients with COPD can be differentiated from their healthy counterparts using tidal breathing patterns 5–10. Therefore, this feasibility study investigated whether parameters derived from SLP – a novel and noncontact, light-based method for measuring tidal breathing – are also able to detect differences between breathing patterns in patients with COPD and subjects with no respiratory disease.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In three of these flow patterns [18][19][20], flow rate was plotted against time. In the remainder [21], the flow pattern was presented as a plot of tidal volume versus time which was numerically integrated to yield flow rate versus time plot after acquisition.…”
Section: Waveform Collectionmentioning
confidence: 99%